2008
DOI: 10.1177/089686080802800606
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Access Planning in Peritoneal Dialysis Patients

Abstract: Peritoneal dialysis (PD) is a well-established renal replacement therapy for end-stage renal disease patients. Nonetheless, on an annual basis, at least 10% of patients shift from PD to hemodialysis for a variety of reasons. Thus the issue of vascular access creation needs to be addressed for this small but significant group of patients. Despite the relatively consistent number of dropouts, the creation of an arteriovenous fistula prior to transfer remains suboptimal, and variable from center to center. Litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 9 publications
2
19
0
2
Order By: Relevance
“…The high use of venous catheters is associated with increased risk for infection and poorer outcomes, 32 underscoring the benefit of early recognition of a trajectory pointed toward transition to HD that can allow for appropriate vascular access planning. 33 Despite certain limitations, studies have demonstrated that routine placement of prophylactic fistulas in PD patients is not successful or justifiable 34 , 35 , 36 , 37 , 38 given their low use and high failure rate when their use is eventually attempted. Improving the ability to predict who may require a transition could enable more patients to benefit from the advantages of an established arteriovenous fistula close to the time of transition to HD, potentially saving them from a tunneled catheter.…”
Section: Discussionmentioning
confidence: 99%
“…The high use of venous catheters is associated with increased risk for infection and poorer outcomes, 32 underscoring the benefit of early recognition of a trajectory pointed toward transition to HD that can allow for appropriate vascular access planning. 33 Despite certain limitations, studies have demonstrated that routine placement of prophylactic fistulas in PD patients is not successful or justifiable 34 , 35 , 36 , 37 , 38 given their low use and high failure rate when their use is eventually attempted. Improving the ability to predict who may require a transition could enable more patients to benefit from the advantages of an established arteriovenous fistula close to the time of transition to HD, potentially saving them from a tunneled catheter.…”
Section: Discussionmentioning
confidence: 99%
“…55 Hence, time-dependent surveillance of effective clearances and ultrafiltration volumes are necessary in patients on PD. Predictive models are needed to identify peritoneal dialysis patients that require transition preparation such as education and vascular access creation, 56,57 particularly to support home hemodialysis when appropriate.…”
Section: Tailoring Timing and Support For Certain Subgroups Of Patientsmentioning
confidence: 99%
“…On an annual basis, at least 10 20% of end stage renal disease patients switch from PD to HD. This conversion should be planned, and it is particularly important to proceed with the creation of a vascular access in these patients 53 . The policy of providing backup fistula in all patients at the time of PD treatment start allowing emergency access for hemodialysis was not successful.…”
Section: Timing Of Hemodialysis Access Placement In Peritoneal Dialysmentioning
confidence: 99%